Strategi Pembelajaran Inkuiri dalam Pendidikan Agama Islam - Yulia Dessani; Wandi Wandi; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The inquiry learning strategy is a pedagogical approach that positions students as active agents in the process of seeking and discovering knowledge. This paper explores the definition, characteristics, underlying principles, advantages, limitations, and implementation stages of the inquiry strategy in learning processes. Rooted in constructivist theory, it emphasizes the value of direct experience and critical thinking in constructing understanding. The analysis reveals that inquiry-based learning enhances students’ critical thinking skills, independence, active participation, motivation, and self-confidence. However, successful implementation requires teachers to be well-prepared in designing meaningful and adaptable instruction. This article recommends applying the inquiry strategy selectively and contextually, especially within Islamic Religious Education, to foster reflective reasoning and character development among students.